Insights into the hotspots and frontiers of research on design for sustainable behavior - Ouyang Lan; Lu Shizhu (Ain Shams Engineering Journal, 2025)
This paper utilizes the scientific knowledge map to explore the current state and emerging trends in the research of sustainable behavior design within the product design domain. It aims to identify cutting-edge developments and innovative directions of Design for sustainable behavior(DfSB) in both theoretical and practical research, offering valuable references for future research and innovative practices. We employed the bibliometric software, including CiteSpace and VOSViewer, analyzing 1,340 research papers related to “sustainable behavior design and product design” collected from the Web of Science database between 2000 and 2024. By combining content analysis with a visual representation of the knowledge map, we examined various factors such as the distribution of authors and research institutions, the evolution of research content, keyword clustering, keyword bursts, and research strategic coordinates. This approach enabled us to discuss the current status, research hotspots, and frontier trends in DfSB research within the product design field. The findings indicate that DfSB −related research has experienced rapid growth over the past two decades, evolving through three distinct stages: the Incipient Period, the Fluctuating Period, and the Surging Period. England was the earliest to initiate DfSB research, while China and the United States currently lead in terms of research output. However, most researchers and research institutions conduct independent studies, suggesting that collaboration intensity in the field needs to be enhanced. Recent research on DfSB focuses on four key areas: (1) the action mechanism of sustainable behavior, emphasizing user motivation and behavior; (2) sustainable design strategies from the perspective of economics and supply chain management; (3) the development of relevant concepts and theories in DfSB; and (4) the application of technologies in DfSB. Despite these advancements, gaps remain in areas such as circular economy, mechanical properties, sustainable materials, emerging technology ethics, cross-cultural theoretical universality, and long-term behavior maintenance mechanisms. These gaps represent significant opportunities for future research. Given the hotspots and development trends identified over the past twenty years, there is substantial potential for future research in interdisciplinary approaches, technological innovations, and more refined studies within the field.